Pengaruh Current Ratio (CR), Debt to Equity Ratio (DER), Return On Asset (ROA), Return On Equity (ROE), dan Earning Per Share (EPS) Terhadap Harga Saham pada Perusahaan Sub Sektor Konstruksi Bangunan yang Terdaftar di Bursa Efek Indonesia Periode 2011-2015 - Rohmatun Nahariyah; Apriatni EP (Jurnal Ilmu Administrasi Bisnis, 2017)
One of the sources of funds obtained by the company comes from the sale of shares. Stock price changes up or down from time to time and it is caused by various factors. This research aims to test the influence of Current Ratio (CR), Debt to Equity Ratio (DER), Return On Asset (ROA), Return On Equity (ROE), and Earning Per Share (EPS) against the stock price on the building construction sector sub companies listed on the Indonesia Stock Exchange period 2011-2015, either partially or simultaneously.The data used in this analysis is the reference point secondary data in the form of annual report and financial report published by IDX. Data analysis technique used in this research is multiple linear regression.Results of the study stated that the CR, DER, ROA, ROE and EPS effect significantly to stock price. And simultaneously there was significant influence between CR, DER, ROA, ROE and EPS against the stock price on the building construction sector sub companies amounting to 72,7%, while the rest of 27,3% is explained by other variables that are not incorporated into the model.Based on the results of the study, the researcher suggested that the building construction sector sub companies to keep their financial performance which includes CR, DER, ROA, ROE and EPS so that stock prices rise. For investors who want to invest in stocks, should pay attention to the factor of EPS, because this research on EPS provide the most powerful influence on the price of the stock.